CORN GRINDING MACHINE MANUFACTURING USES ELECTRIC POWER AND HUMAN POWER - Muchamad Dicky Sobirin, Muchamad Dicky Sobirin; Prantasi Harmi Tjahjanti, Prantasi Harmi Tjahjanti (Universitas Nahdlatul Ulama Surabaya, 2024)
The issue with maize is that kernel size is frequently not the same as grain size if you want the grains or seeds to be fine. Building a basic corn-grinding machine with electricity and human power in case of an electrical outage is the community service that was completed. The process begins with the design of a corn grinding machine, is followed by the construction of the machine and testing, specifically grinding performance tests for different capacities of 3 kg, 4 kg, and 5 kg of corn utilizing both electric and manual power. The findings of a 60-minute human-powered corn grinding machine performance test showed that the maximum ground corn grinding was fine, weighing 20 kg of ground corn with a fairly excellent grinding of corn granules/seeds. In the meantime, 30 kg of corn were weighed during the electric corn grinder's performance test in 60 minutes, and the machine's grinding of maize grains and ores was reasonably successful. Keywords: Maize kernels or seeds; corn grinder; machine performance evaluation; labor-intensive Human power; electricity power